The role of school governance in the democratization of public school with reference to kwaCeza circuit in Kwazulu Natal Province - Ndlela, Bongiwe Prudence (University of the Free State, 2015)
Abstract not available
Dissertation (MGT (Governance and Political Transformation))--University of the Free State, 2015
Keywords: South Africa; Education; Democracy; Governance